KEMAMPUAN BERPIKIR DIVERGEN, ADVERSITY QUOTIENT, SIKAP TERHADAP MATEMATIKA, PERSEPSI TENTANG CARA MENGAJAR GURU, MOTIVASI DAN HASIL BELAJAR MATEMATIKA - Nurjannah Nurjannah; Nurdin Arsyad; Muhammad Darwis (Vidya Karya, 2018)
Abstract. This ex post facto study aimed to reveal the influence of divergent thinking skills, adversity quotient, attitudes toward mathematics, and perceptions of how mathematics teachers teach on learning outcomes and motivation to learn mathematics. The population of this study was all of eighth graders of Public Junior High School (SMPN) in the whole Sub District of North Wara, Palopo City. The sample was determined by cluster random sampling. The instruments used were questionnaires and tests. The research data were analyzed by using SPSS statistical data processing program. The results showed that divergent thinking skills, adversity quotient, attitudes toward mathematics, and perceptions of how mathematics teachers teach, together or partially, had a significant effect on mathematics learning outcomes and motivation to learn mathematics of Public Junior High School 8th graders in the whole District of North Wara, Palopo City. Keywords: Divergent Thinking skills, Adversity Quotient, Attitudes toward mathematics, Perception, Motivation, and mathematics learning outcomes. Abstrak.  Penelitian ex post facto ini bertujuan untuk mengungkap pengaruh kemampuan  berpikir Divergen,  adversity quotient, sikap terhadap matematika, dan persepsi terhadap cara mengajar guru matematika terhadap hasil belajar dan motivasi belajar matematika. Populasi dari penelitian ini adalah seluruh siswa kelas VIII SMPN se-Kecamatan Wara Utara, Kota Palopo. Penentuan sampel dilakukan dengan cluster random sampling. Instrumen yang digunakan berupa angket dan tes. Data dianalisis menggunakan program pengolahan data statistik SPSS. Hasil penelitian menunjukkan bahwa kemampuan berpikir divergen, adversity quotient, sikap terhadap matematika, dan persepsi tentang cara guru matematika mengajar secara bersama-sama maupun secara parsial berpengaruh secara signifikan terhadap hasil dan motivasi belajar matematika pada siswa Kelas VIII SMPN se-Kecamatan Wara Utara, Kota Palopo. Kata Kunci: Berpikir divergen, adversity quotient, sikap, persepsi, motivasi, dan hasil belajar matematika.